Physical-chemical and microbiological analysis of water of irrigation and microbiological analysis of lettuce (Lactuca sativa) - Bierhas, Camila Corrêa; Machado, Aline Belem; Picoli, Simone Ulrich; Osorio, Daniela Montanari Migliavacca; Berlese, Daiane Bolzan (Ciência e Natura, 2019)
The contamination of vegetables by pathogenic microorganisms is directly related to the water quality used in their irrigation. Lettuce is the main vegetable consumed in Brazil and because it does not undergo any processing before its consumption, it is directly affected by the quality of the water used for irrigation. This study analyzed the physical-chemical and microbiological quality of water used in lettuce irrigation and possible microbiological contamination of lettuce. In relation to microbiological analyzes, high values were found for heterotrophic bacteria and total coliforms in weirs and vegetables. For fecal coliforms, in almost all water samples, the value found was above that established by the legislation. In lettuce, this occurred in three samples. No strong correlation was found between water and lettuce contamination. In relation to the physicochemical parameters analyzed, only the value of the turbidity in one of the weirs was above the threshold established by the legislation.